Magnitude and Risk of Dying among Low Birth Weight Neonates in Rural Ethiopia: A Community-Based Cross-Sectional Study - Akine Eshete; Abebe Alemu; Taddes Alemu Zerfu (International Journal of Pediatrics)
Background. Even if remarkable progress has been made in reducing preventable child deaths worldwide, neonatal mortality reduction has remained unsatisfactory. Low birth weight (LBW) is the major risk factor for child deaths during the neonatal period, yet only 5% of babies are weighed at birth in Ethiopia. The aim of the present study was to determine the magnitude and risk of dying among low birth weight neonates in rural Gedeo, Southern Ethiopia. Methods. Community-based mixed-method approach design was employed between September and October 2016 to identify and enroll study participants in rural Gedeo, Southern Ethiopia. Records of 17,503 live birth babies, of whom 2,065 (11.8%) had LBW, born in the last 12 months were screened to identify 885 (42.8%) biological mother–LBW neonate pairs from eight health centers. The study subjects were randomly selected using a multistage stratified cluster sampling technique. Cox proportional hazards regression model was used to predict maternal and neonatal risk factors associated with the risk of neonatal death. Results. The overall neonatal mortality rate (NMR) among LBW infants was 110 per 1000 live births (95% confidence interval: 75 –228). Close to half, 374 (42.3%), of the LBW neonates died during the first week of life. The estimated hazard ratios of mortality were higher among neonates whose mothers did not attend antenatal care (ANC) (HR=1.58, 95 % CI: 1.02-2.43), gave birth by assisted or cesarean delivery (HR=1.81 and 3.72; 95% CI: 1.10 - 3.02 and 2.11-6.55), and experienced some form of illness during pregnancy (HH=3.34, 95 % CI: 2.11-5.29), respectively. Similarly, neonates born with very low (<2000gm) birth weight and born prematurely (before 37 weeks of gestation) carried a higher (HR= 1.90 and 1.47; 95 % CI: 1.22 - 2.96 and 1.07-2.28) risk of death. On the other hand, maternal formal education was found to be the single protective factor (HR= 0.65,95 % CI: 0.43-0.99). Conclusion. Nearly one in every ten (11%) of neonates die before celebrating their firth month of life, mainly during the first week in rural Ethiopia. The risk of dying from LBW during the neonatal period is almost fourfold of the current estimated national NMR. Maternal obstetric characteristics and fetal maturity were predictors of mortality.